Inflammation-associated depression: From serotonin to kynurenine - Dantzer, Robert; O’Connor, Jason C.; Lawson, Marcus A.; Kelley, Keith W. (Psychoneuroendocrinology, 2011)
In the field of depression, inflammation-associated depression stands up as an exception since its causal factors are obvious and it is easy to mimic in an animal model. In addition, quasi-experimental studies can be carried out in patients who are treated chronically with recombinant cytokines for a medical condition since these patients can be studied longitudinally before, during and after stimulation of the immune system. These clinical studies have revealed that depression is a late phenomenon that develops over a background of early appearing sickness. Incorporation of this feature in animal models of inflammation-associated depression has allowed the demonstration that alterations of brain serotoninergic neurotransmission do not play a major role in the pathogenesis. This is in contrast to the activation of the tryptotphan degrading enzyme indoleamine 2,3-dioxygenase that generates potentially neurotoxic kynurenine metabolites such as 3-hydroxy kynurenine and quinolinic acid. Although the relative importance of peripherally versus centrally produced kynurenine and the cellular source of production of this compound remain to be determined, these findings provide new targets for the treatment of inflammation-associated depression that could be extended to other psychiatric conditions mediated by activation of neuroimmune mechanisms.